Analisis Efektivitas dan Efisiensi Supply Chain Management pada Regional 1 Pelindo Belawan - Alghani, Muhammad Rafi; Marwan, Marwan (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Ports play a strategic role as hubs of maritime transportation, centers of goods distribution, and drivers of regional economic growth. Regional 1 PT Pelabuhan Indonesia (Persero) Belawan is one of the key ports in Indonesia, equipped with modern infrastructure to support logistics activities, particularly container handling. The effectiveness of transportation services in this port is strongly influenced by the quality of infrastructure, transportation systems, and coordination among stakeholders. Along with the increasing flow of containers and the dynamics of globalization, an integrated supply chain management system has become essential to ensure efficiency, safety, and speed in goods distribution. This study aims to measure the performance and achievement of the company’s operational indicators by applying the Supply Chain Operations Reference (SCOR) model. Performance measurement was conducted through the validation of Key Performance Indicators (KPI), weighting using the Analytical Hierarchy Process (AHP), and score normalization with Snorm De Boer. The SCOR model covers five core processes—plan, source, make, deliver, and return—focusing on two main attributes, namely reliability and responsiveness.